Deconstructing the self and reshaping perceptions: An intensive whole-brain 7T MRI case study of the stages of insight during advanced investigative insight meditation - Winson F.Z. Yang; Avijit Chowdhury; Terje Sparby; Matthew D. Sacchet (NeuroImage)
The stages of insight (SoI) are a series of psychological realizations experienced through advanced investigative insight meditation (AIIM). SoI provide a powerful structured framework of AIIM for understanding and evaluating insight-based meditative development through changes in perception, experiences of self, cognition, and emotional processing. Yet, the neurophenomenology of SoI remains unstudied due to methodological difficulties, rarity of suitable advanced meditation practitioners, and dominant research emphasis on attention-based meditative practices. We investigated the neurophenomenology of SoI in an intensively sampled adept meditator case study (4 hr 7T fMRI collected in 26 runs with concurrent phenomenology) who performed SoI and rated specific aspects of experience immediately thereafter. Linear mixed models and correlations were used to examine relations among the cortex, subcortex, brainstem, and cerebellum, and SoI phenomenology. We identified distinctive whole-brain activity patterns associated with specific SoI, and that were different from two non-meditative control states. SoI consistently deactivated regions implicated in self-related processing, including the medial prefrontal cortex and temporal poles, while activating regions associated with awareness and perception, including the parietal and visual cortices, caudate, several brainstem nuclei, and cerebellum. Patterns of brain activity related to affective processing and SoI phenomenology were also identified. Our study presents the first neurophenomenological evidence that SoI shifts and deconstructs self-related perception and conceptualization, and increases general awareness and perceptual sensitivity and acuity. Our study provides SoI as a foundation for investigative, and advanced meditation in particular.